The Islamic-Hindu conflict over the Babri Mosque in India (Historical study) - Hamid Abu Shanna, Asaad (Journal of College of Education, 2020)
The issue of the Babri Mosque in India, built by the Mughal emperor Dhahiruddin Muhammad Babar in 1528, is an important and sensitive issue that had important implications for the political reality in India after partition in 1947 because of the employment of Hindu and Islamic political and religious parties for various purposes: The Babari Mosque has been preoccupied with Indian public opinion throughout the second half of the twentieth century, and has caused a great public and public record. Hindu political and religious circles have claimed that the Babri Mosque is only a historical temple with a high religious value. He was born in Ram, one of their followers according to their religious beliefs. Babar, when he conquered India and defeated his Hindu enemies in the sixteenth century, ordered the destruction of the temple and the construction of a mosque instead of it. Britain had a hand in stirring up this problem through some British writers who promoted such a story, Relying on the correct historical evidence, but the archaeological excavations that were invoked in the seventies of the twentieth century denied the existence of a temple at the site of the Babri mosque, but the Hindu political parties exploited the religious sentiment among the masses, and raised slogans calling for the demolition of the Babri Mosque and the restoration of ownership and The mosque was demolished in 1992 under the eyes of the official government authorities, and bloody clashes between Muslims and Hindus killed hundreds of people in various parts of India.